St. Louis encephalitis virus possibly transmitted through blood transfusion—Arizona, 2015. Issue 12 (14th September 2017) - Venkat, Heather; Adams, Laura; Sunenshine, Rebecca; Krow‐Lucal, Elisabeth; Levy, Craig; Kafenbaum, Tammy; Sylvester, Tammy; Smith, Kirk; Townsend, John; Dosmann, Melissa; Kamel, Hany; Patron, Roberto; et al.
Abstract : BACKGROUND: St. Louis encephalitis virus is a mosquito‐borne flavivirus that infrequently causes epidemic central nervous system infections. In the United States, blood donors are not screened for St. Louis encephalitis virus infection, and transmission through blood transfusion has not been reported. During September 2015, St. Louis encephalitis virus infection was confirmed in an Arizona kidney transplant recipient. An investigation was initiated to determine the infection source. STUDY DESIGN AND METHODS: The patient was interviewed, and medical records were reviewed. To determine the likelihood of mosquito‐borne infection, mosquito surveillance data collected at patient and blood donor residences in timeframes consistent with their possible exposure periods were reviewed. To investigate other routes of exposure, organ and blood donor and recipient specimens were obtained and tested for evidence of St. Louis encephalitis virus infection. RESULTS: The patient presented with symptoms of central nervous system infection. Recent St. Louis encephalitis virus infection was serologically confirmed. The organ donor and three other organ recipients showed no laboratory or clinical evidence of St. Louis encephalitis virus infection. Among four donors of blood products received by the patient via transfusion, one donor had a serologically confirmed, recent St. Louis encephalitis virus infection. Exposure to an infected mosquito was unlikely based on the patient's minimal outdoor exposure. In addition, no St. Louis encephalitis virus‐infected mosquito pools were identified around the patient's residence. CONCLUSION: This investigation provides evidence of the first reported possible case of St. Louis encephalitis virus transmission through blood product transfusion. Health care providers and public health professionals should maintain heightened awareness for St. Louis encephalitis virus transmission through blood transfusion in settings where outbreaks are identified.